Interdisciplinary Team Teaching A Collaborative Study of High-Impact Practices - Lansiquot, Reneta D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book explores the community of practice at New York City College of Technology engaged in interdisciplinary team teaching. Professors report on their high-impact practices when they combine the assets of different disciplines. Chapters feature examples of the innovative curriculum resulting from a true interdisciplinary system, including place-based learning. The book also discusses questions of validity and measuring the influence of high-impact practice within interdisciplinary co-teaching.
1. The Art and Science of Interdisciplinary Connections: A Look at Dental and Dental Hygiene Education -- 2. Demystifying the Kitchen: A Collaborative Interdisciplinary Study of Science in the Kitchen -- 3. Place-Based Learning as a High-Impact Educational Practice -- 4. Learning Places: Place-Based Learning in an Interdisciplinary Approach to Undergraduate Research -- 5. Using Monuments to Teach About Racism, Colonialism, and Sexism -- 6. Deconstructing the Heritage of Imperialism Toward Life-Long Learning: High-Impact Practices That Further Student Self-Actualization and Social Justice Analyses -- 7. A Psychologist's Perspective for Coordinating Interdisciplinary Courses.
Keywords: Teaching; Higher education; Professional education; Vocational education; Career education; Education; Teaching and Teacher Education; Higher Education; Professional & Vocational Education; Career Skills; Education, general